2022
DOI: 10.3390/agronomy12102434
|View full text |Cite
|
Sign up to set email alerts
|

Use of Phosphonate Salts to Control Chestnut ‘Brown Rot’ by Gnomoniopsis castaneae in Fruit Orchards of Castanea sativa

Abstract: The fungus Gnomoniopsis castaneae is the causal agent of the “brown rot” of sweet chestnut fruits. These days, this pathogen represents one of the main limiting factors for the sustainability of fruit production worldwide. Although heat treatment post-harvest is efficient in completely inactivating the pathogen, the application of appropriate protocols to control “brown rot” in chestnut orchards is required to help in reducing the latent population of the fungus in fruit tissues, and the consequent development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Since scientific evidence shows that phosphonates have no nutritional role in the plant to justify their use as fertilizer, recently, the European Directive EU 1009/2019 has restricted their use, with a ban on their use in both conventional and organic agriculture. Therefore, any new formulation based on phosphonate will be registered as a pesticide/fungicide on target crops/plants [ 60 ]. Currently in Italy K-phosphonate is registered on seven fruit bearing trees, tomato and grape.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since scientific evidence shows that phosphonates have no nutritional role in the plant to justify their use as fertilizer, recently, the European Directive EU 1009/2019 has restricted their use, with a ban on their use in both conventional and organic agriculture. Therefore, any new formulation based on phosphonate will be registered as a pesticide/fungicide on target crops/plants [ 60 ]. Currently in Italy K-phosphonate is registered on seven fruit bearing trees, tomato and grape.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, treatments of K-phosphonate must also consider the Maximum Residue Limit (MRL) recently issued by EU Regulation 2021/1807, which increases the limit for chestnut fruits to 1500 mg/kg. Considering the efficacy of K-phosphonate against other important pathogens on sweet chestnut, such as Gnomoniopsis castanea [ 60 ], further research focused on residue values after treatments is needed. Previous studies reported lower values than those issued by the EU regulation 2021/1807 [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical control in chestnuts is not a current practice, and no fungicides are regulated for Gs control, although some studies have suggested the potential use of pyraclostrobin, difenoconazole, and phosphonate salts [14,15]. However, chemical fungicides generally depend on very limited and directed modes of action and are associated with resistance acquisition by pathogens.…”
Section: Introductionmentioning
confidence: 99%